2009
DOI: 10.1007/s10751-009-0116-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and soft magnetic properties of FINEMET type alloys: Fe73.5Si13.5Nb3 − x Mo x B9Cu1 (x = 1.5, 2)

Abstract: FINEMET type ribbons (Fe 73.5 Si 13.5 Nb 3−x Mo x B 9 Cu 1 , x = 1.5, 2 at.%) were produced by the planar flow casting technique and subsequently heat treated at 823 K to induce nanocrystallization and to optimize its soft magnetic properties. The coercivity, measured by conventional fluxmetric method, resulted in H C = 0.53 ± 0.10 and 0.41 ± 0.05 A/m for x = 1.5 and 2 respectively. A correlation between magnetic properties and the amorphous and nanocrystalline phases when Nb was partially substituted with Mo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Previous results on the study of these alloys showed that the replacement of Nb for Mo increased both the crystalline fraction and the amount of Si in the nanograins when the heat treatment was kept at 813 K for 1 h [16]. Based on these two facts, we would have expected a decrease of the l S for these treated alloys with Mo addition, since l S sensitively depends on the crystal fraction and on l S,Cr (l S of the crystalline phase), which varies with Si content in the grains [11].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous results on the study of these alloys showed that the replacement of Nb for Mo increased both the crystalline fraction and the amount of Si in the nanograins when the heat treatment was kept at 813 K for 1 h [16]. Based on these two facts, we would have expected a decrease of the l S for these treated alloys with Mo addition, since l S sensitively depends on the crystal fraction and on l S,Cr (l S of the crystalline phase), which varies with Si content in the grains [11].…”
Section: Resultsmentioning
confidence: 96%
“…Based on these two facts, we would have expected a decrease of the l S for these treated alloys with Mo addition, since l S sensitively depends on the crystal fraction and on l S,Cr (l S of the crystalline phase), which varies with Si content in the grains [11]. However, l S also depends on l S,Am (l S of the amorphous phase) which in turn varies with the composition of the amorphous remaining matrix and its change with Nb/Mo rate has been reported [16]. Measured l S values showed no trend with the exchange of refractory elements neither for the asquenched ( $ 19 ppm) nor for the annealed samples ( $ 2 ppm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies, Nb was substituted by other elements such as V, Cr, Mo, etc. . In the literature , Silveyra et al studied Fe 73.5 Si 13.5 B 9 Nb 3− x Mo x Cu 1 ( x = 1.5, 2, at.%) alloys annealed at a fixed temperature and time by Mossbauer spectrum method.…”
Section: Introductionmentioning
confidence: 99%
“…. In the literature , Silveyra et al studied Fe 73.5 Si 13.5 B 9 Nb 3− x Mo x Cu 1 ( x = 1.5, 2, at.%) alloys annealed at a fixed temperature and time by Mossbauer spectrum method. The results indicated that H c was decreased due to the reduction on the effective anisotropy constant, and the crystalline fraction in Mo‐doped Finemet increased.…”
Section: Introductionmentioning
confidence: 99%